TiO2 Nanowires from Wet-Corrosion Synthesis for Peptide Sequencing Using Laser Desorption/lonization Time-of-Flight Mass Spectrometry - Kim, Mira; Park, Jong-Min; Yun, Tae Gyeong; Noh, Joo-Yoon; Kang, Min-Jung; Pyun, Jae-Chul (American Chemical Society, 2018)
In this work, TiO2 nanowires synthesized from a wet-corrosion process were presented for peptide sequencing by photocatalytic reaction with UV radiation. For the photocatalytic decomposition of peptides, the peptide sample was dropped on a target plate containing synthesized TiO2 nanowire zones and UV-irradiated. Subsequently, the target plate was analyzed by laser desorption/ionization time-of flight (LDI-TOF) mass spectrometry using the synthesized TiO2 nanowires as a solid matrix. The feasibility of peptide sequencing based on the photocatalytic reaction with the synthesized TiO2 nanowires was demonstrated using six types of peptides GHP9 (G(1)-H-P-Q-G(2)-K-1-K-2-K-3-K-4, 1006.59 Da), BPA-1(K-1-S-1-L-E-N-S-2-Y-G(1)-G(2)-G(3)-K-2-K-3-K-4, 1394.74 Da), PreS1(F-1-G-A-N-1-S-N-2-N-3-P-1-D-1-W-D-2-F-2-N-4-P-2-N-5, 1707.68 Da), HPQ peptide-1 (G-Y-H-P-Q-R-K, 884.45 Da), HPQ peptide-2 (K-R-H-P-Q-Y-G, 884.45 Da), and HPQ peptide-3 (R-Y-H-P-Q-G-K, 884.45 Da). The identification of three different peptides with the same molecular weight was also demonstrated by using the synthesized TiO2 nanowires for their photocatalytic decomposition as well as for LDI-TOF mass spectrometry as a solid-matrix.
Keywords: PARYLENE-MATRIX CHIP; TITANIUM-OXIDE NANOTUBE; SMALL MOLECULES; SOLID-MATRIX; STRUCTURAL-CHARACTERIZATION; DESORPTION-IONIZATION; SUSCEPTIBILITY TEST; STEEL TARGETS; NANOPARTICLES; DIOXIDE